(untitled) (HISKIA : Jurnal Ilmu Kimia & Pendidikan Kimia, 2025)
Abstract This study aims to analyze the quality of East Nusa Tenggara (NTT) ethnoscience-based chemistry skill assessment instruments from the perspective of chemistry education students. These instruments are designed to measure scientific process skills, higher-order thinking skills (HOTS), and understanding of chemistry concepts integrated with NTT local wisdom. The research method used was quantitative descriptive with a survey design. The research subjects were active students in the Chemistry Education Study Program who had developed similar instruments. Data were collected using a questionnaire with a 5-point Likert scale and analyzed using descriptive statistics to obtain mean values and quality categories. The results showed that the instruments developed by the students generally had good quality in various aspects. In terms of alignment with learning objectives, the instruments showed adequate to good quality, although the measurement of higher-order thinking skills (HOTS) still requires improvement. The relevance of NTT ethnoscience to chemical concepts also showed good quality, particularly in terms of integration and scientific accuracy. The validity aspects, especially content and face validity, were categorized as good to very good, while construct validity was adequate. The reliability of the instruments showed fairly good to good quality, with strong assessment objectivity. Furthermore, the format and language aspects of the instruments were rated as good to very good, supported by clear instructions and good layout. Finally, the feasibility of implementing the instruments showed good quality, reflecting time efficiency, utilization of local resources, and suitability for the educational level. The conclusion indicates that this instrument has great potential as a valid and reliable measurement tool in the context of NTT ethnoscience-based chemistry learning